Wristwatch PCR: A Versatile and Efficient Genome Walking Strategy - Wang, Lingqin; Jia, Mengya; Li, Zhaoqin; Liu, Xiaohua; Sun, Tianyi; Pei, Jinfeng; Wei, Cheng; Lin, Zhiyu; Li, Haixing (Frontiers in Bioengineering and Biotechnology, 2022)
Genome walking is a method used to retrieve unknown flanking DNA sequence. Here, we report wristwatch (WW) PCR, an efficient genome walking technique mediated by WW primers (WWP). The WWPs feature identical 5’-ends (12 bp) and 3’-ends (3 bp), as well as heterologous intervals (10 bp). Therefore, the WWPs can partially hybridize with each other’s complement under low temperature to form a wristwatch-like structure. Each WW-PCR set comprises of three nested (primary, secondary, and tertiary) PCRs individually participated by three WWPs. The WWP arbitrarily anneal to somewhere on DNA template in the one low-stringency cycle of primary PCR, or directionally to the previous WWP site in the one reduced-stringency cycle of secondary/tertiary PCR, producing a pool of single-stranded DNAs (ssDNA). A target ssDNA incorporates gene-specific primer (GSP) complement at the 3’-end and the WWP at the 5’-end, thus can be exponentially amplified in the next high-stringency cycles; nevertheless, a non-target ssDNA cannot be amplified as it lacks perfect binding site for any primers. The practicability of WW-PCR was validated by successfully accessing unknown regions flanking glutamate decarboxylase gene locus of Lactobacillus brevis CD0817 and hygromycin gene of rice. WW-PCR is an attractive alternative to the existing genome walking techniques.